Concentration of Potassium, Magnesium, and Iron of Brachiaria humidicola (Rendle Schweick) at Various Cultivation Methods and Defoliation Intervals - Mansyur, Mansyur; Djuned, Harun; Dhalika, Tidi; Abdullah, Luki (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2006)
The existence of weeds significantly decreases the rate of production and quality of herbage. Physical weed control by defoliation could be expected to sustain quality and production of herbage, and is able to control weeds expansion. The aims of this study were to know the effect of defoliation intervals of B. humidicola that invited by C. odorata and its effect on potassium, magnesium and iron concentration. The experiment was conducted at the Laboratory of Agrostology, Faculty of Animal Science, Bogor Agricultural University. Chemical composition of forage was analyzed at the Chemistry Laboratory, Center of Soil and Agroclimatology Research. Split Plot Design in Time was used in the field experiment. The treatments were nine different planting methods and different defoliation intervals. Defoliation times were divided on the first defoliation and the last defoliation. The results of this experiment showed that potassium, magnesium and iron concentrations of herbage which were defoliated every 30 days was significantly higher than those defoliated every 60 days and 90 days. Potassium and iron concentrations at the last defoliation were higher than the first defoliation. The existence of C. odorata decreased magnesium and iron concentration of B. humidicola herbage, although they were defoliated together with grass defoliation. Key Words: Potassium, magnesium, iron, herbage, defoliation interval